Nitrogen fertilization strategies to increase yield and protein of wheat in the pampean semiarid region (Semiárida, 2019)
The objective of this work was to evaluate the influence of nitrogen fertilization on the expression of yield and grain protein content in wheat in different environments of the semiarid Pampa region. The field experiments were carried out in Embajador Martini, Macachín and Anguil. The treatments were: control (0N), fertilization at seeding with 40 kg N.ha-1 (40+0) and 80 kg N.ha-1 (80+0), delayed fertilization with 40 kg N.ha-1 (between Z3.9 and Z5.0) (0+40) and divided fertilization (40+40). The treatments were arranged in a completely randomized block design with four replicates. Five filed experiments were carried out in each site and yield, grain protein content, water use efficiency and nitrogen use efficiency were determined. The sites with IMO> 4.5% had more response to yields in comparation with control, than the sites with IMO> 4.5%. The soils with >50% A+L had grater soil potential fertility, and there were significant differences between the control and 80 kg.ha-1 at seeding o divided fertilization. Instead, the soils with
Keywords: soil texture; nitrogen use efficiency; divided fertilization